International Experience and Theoretical Concepts of Improving the Wellbeing of Uzbekistan’s Rural Women - Azizova Nodira Mannapovna; Bekmurodov Mansur Bobomurodovich (Genius Journals, 2023)
This article provides the literature review of the international experience and theoretical concepts of improving the welfare of rural women taking into consideration objective and subjective indicators. It was revealed that the concept of rural women empowerment is an important element of public policy aimed at empowering citizens at the community, regional and national levels. The Government of Uzbekistan prioritized the implementation of the gender policy based on the principles of inclusion and equal access to natural, financial and technological resources. By adapting the international concept of the Leaky bucket the author developed the Gender Action and Community Development Plan for community as well as presented the ways of poverty reduction and increasing the wellbeing of rural women in Uzbekistan.
Keywords: rural women; gender equality; wellbeing; Uzbekistan